Loitsud ja rahvaarstid Virumaal - Mare Kõiva (Mäetagused, 2017)
On the basis of Virumaa material, the article discusses healing words as well as charms that were used to regulate communication between human beings and the world of spirits. Healing words richly varied in form made use of fragments of prayers, Bible texts, and hymnals, and were based on legend material, allusions, and mythic worldview. The article gives an overview of a) the relationship between oral and written lore in charm tradition, connections with fictional and real books of wisdom; b) exchange of language codes; c) regulations of word-magic behaviour; d) healing charms and charms regulating social relations, housekeeping, and humans’ relationship with nature. The second half of the article discusses changes in healers’ healing tradition. During the past century, folk medicine integrated knowledge from different schools, and the importance of alternative and complementary medicine, such as yoga, Chinese medicine, Ayurveda, and music therapy (most of these cosmopolitan), increased. So we can conclude that cosmopolitan folk medicine exists side by side with official medicine. Another significant trend rising to the fore highlights the importance of local folk medicine, which emphasises traditional values and creates novel cultural interpretations. To characterise the changes, the article introduces four healers, ranging from a half-mythic witch-herder to the healers-innovators of medical methods and local culture.